Study on synthesis under microwave irradiation and cytotoxic activity of some dibenzo(perhydrotriazino)aza-14-crown-4-ether derivatives - Anh, Lê Tuấn; Tùng, Tô Hải; Hiếu, Trương Hồng; Thanh Vân, Trần Thị; Thymophievich, Soldatenkov Anatoly (Vietnam Journal of Science and Technology, 2015)
Nowadays, chemistry of azacrown ethers are being interested by many researchers, especially with derivatives containing perhydrotriazine moiety and crown ether cycle. In previous publications, we have been firstly mentioned on the method affording dibenzo(perhydrotriazino)aza-14-crown-4 ether derivatives from condensation reaction of polyether (I) with thioure or guanidine in the presence of ammonium acetate at room temperature. The yield of this reaction achieved about 73% in acetic acid. However, the time of this reaction is still long, lasted about 13h. It has limited practical applications of these compounds. Therefore, for optimising the synthetic method, in this report, we have done successfully this reaction by using irradiated energy without catalyst of acetic acid as normal way at conditions: 200W, 500C, 20 minutes.  The analytic resutls of   physicochemical constants and spectrocospic data showed that the obtained substances from two methods are the same. (Perhydrotriazino)aza-14-crown-4 ether derivatives have been then tested biological activities.